Animated Video Media Used to Improve Grade VIII Students’ Listening Comprehension of Descriptive Texts: A Classroom Action Research at SMP Al Umar, Ogan Ilir Regency in The Year of 2025 - Lestari, Endang; Rosidi, Rosidi (International Journal of English and Applied Linguistics (IJEAL), 2025)
This research examines the effectiveness of animated video media in enhancing Grade VIII students’ listening comprehension of descriptive texts at SMP Al Umar, Ogan Ilir Regency, during the 2025 academic year. A classroom action research (CAR) design was implemented over two cycles, each consisting of planning, implementation, observation, and reflection stages. Data were obtained through listening comprehension tests, classroom observations, and student interviews. In the pre-cycle stage, only 12 students (40%) achieved the Minimum Mastery Criteria (MMC) score of 70, while 18 students (60%) fell below the standard. In Cycle I, the number of students meeting the MMC increased to 22 (73%), with 8 students (27%) still underperforming. By Cycle II, mastery rose substantially to 27 students (90%), leaving only 3 students (10%) below the benchmark. These results demonstrate that the integration of animated video media significantly improves students’ listening comprehension and fosters greater engagement in English language learning, particularly in the context of descriptive text instruction.